AlN/GaN HEMTs grown by MBE and MOCVD: Impact of Al distribution. Issue 8 (3rd July 2017) - Godejohann, Birte‐Julia; Ture, Erdin; Müller, Stefan; Prescher, Mario; Kirste, Lutz; Aidam, Rolf; Polyakov, Vladimir; Brückner, Peter; Breuer, Steffen; Köhler, Klaus; Quay, Rüdiger; Ambacher, Oliver
Abstract : Binary AlN/GaN high electron mobility transistors (HEMTs) were grown by plasma‐assisted molecular beam epitaxy (PA‐MBE) as well as metal‐organic chemical vapor deposition (MOCVD) and compared with regard to their structural and electrical properties. The investigated structures differ in Al distribution and composition of the AlN barrier due to characteristic differences of the two growth methods such as growth temperature and interface sharpness. While we observe a nearly pure AlN layer and an abrupt interface for MBE growth, a graded "AlN" barrier with a significant amount of Ga is found for the MOCVD grown structures which is reflected by the electrical properties of the HEMT structures. Si‐implanted ohmic contacts were formed on MBE as well as MOCVD grown structures. The activation anneal step subsequent to implantation at temperatures ∼1100 °C changes the observed Al profiles of MBE structures and damages the active region, whereas MOCVD samples react insensitively and thus were able to be further processed. A maximum drain current of ∼1.46 A mm −1 at a gate source voltage of +3 V is observed for the processed devices. A current‐gain cut‐off frequency of 89 GHz and maximum oscillation frequency of 208 GHz were measured, which demonstrate an excellent small‐signal performance of AlN/GaN devices with 100 nm gate length.